Cost-Effectiveness Of Mobile Phone Imaging Teledentistry (Mpit) For Early Detection Of Oral Cancer In Malaysia: A Markov Decision Analysis Approach - Raman, Sivaraj (2022)
Although numerous national oral cancer screening initiatives are carried out in Malaysia, patients are still being disproportionately diagnosed at later stages, leading to substantial social and economic burdens. To overcome these challenges, a novel application called MeMoSA® was developed by incorporating a mobile phone imaging teledentistry for oral examinations (MOE). The application serves as a communication platform between primary healthcare practitioners and specialists located off-site. This study aims to report the cost-effectiveness of MOE, for screening patients with oral potentially malignant disorders (OPMD) and oral cancer compared to the conventional oral examination (COE) conducted routinely via either high-risk community screening camps (C1) or primary dental clinics (C2). A societal perspective was adopted to encompass all the far-reaching consequences of early detection of oral cancer. A Markov modeling was applied to simulate the impact of various MOE screening strategies on cost and quality-adjusted life-years (QALYs) for a hypothetical cohort of 100,000 adults aged 40 years. The initial findings from two tertiary healthcare centers demonstrated that late-stage oral cancer incurred significantly higher healthcare provider and patient household costs, in addition to a lower quality of life compared to the early stage and OPMD.